2022
DOI: 10.3390/membranes12070653
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thin Film Nanocomposite Membranes Based on Chitosan Succinate Modified with Fe-BTC for Enhanced Pervaporation Dehydration of Isopropanol

Abstract: The application of environmentally friendly and energy-efficient membrane processes allows improvement the ecological safety and sustainability of industrial production. However, the effective application of membrane processes requires novel high-performance thin film composite (TFC) membranes based on biopolymers to solve environmental problems. In this work for the first time novel thin film nanocomposite (TFN) membranes based on biopolymer chitosan succinate (ChS) modified with the metal organic framework i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…The ChS or ChS-Fe-BTC interlayer was deposited on the surface of a porous membrane substrate via the dynamic technique (dead-end ultrafiltration of aqueous ChS solution or ChS-Fe-BTC aqueous dispersion, through a porous PAN membrane). The structure, physicochemical properties, and pervaporation performance of ChS/PAN and ChS-Fe-BTC TFC membranes were discussed in detail in [ 83 ]. It was found that the introduction of 30 wt % of Fe-BTC with respect to the ChS weight yields an increase in the thickness of the membrane selective layer (from 0.44 to 4.53 µm), along with the roughness (average surface roughness (R a ) increased from 3.44 to 8.95 nm) and water contact angle (increased from 30 ± 2° to 36 ± 2°) of the selective layer surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ChS or ChS-Fe-BTC interlayer was deposited on the surface of a porous membrane substrate via the dynamic technique (dead-end ultrafiltration of aqueous ChS solution or ChS-Fe-BTC aqueous dispersion, through a porous PAN membrane). The structure, physicochemical properties, and pervaporation performance of ChS/PAN and ChS-Fe-BTC TFC membranes were discussed in detail in [ 83 ]. It was found that the introduction of 30 wt % of Fe-BTC with respect to the ChS weight yields an increase in the thickness of the membrane selective layer (from 0.44 to 4.53 µm), along with the roughness (average surface roughness (R a ) increased from 3.44 to 8.95 nm) and water contact angle (increased from 30 ± 2° to 36 ± 2°) of the selective layer surface.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of ChS/MA aqueous solutions, as well as the formation of a ChS interlayer on the PAN membrane-support in the dynamic mode, were reported in our previous work [ 83 ]. Briefly, a ChS interlayer on the surface of the porous PAN membrane support was formed using an aqueous solution containing 1.0 wt % ChS and 0.15 wt % maleic anhydride (MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed matrix membranes with MOFs as modifiers are promising for application in pervaporation due to the unique structural properties of MOFs, ease of modification, as well as good compatibility between MOFs and the polymer matrix. To develop pervaporation membranes, MOFs were used to modify polymers such as polyimide [ 27 , 28 ], cardo polyetherketone [ 29 ], polyether-block-amide [ 30 ], polyarylethersulfone [ 31 ], chitosan [ 32 , 33 , 34 ], a polymer of intrinsic microporosity PIM-1 [ 35 ], polydimethylsiloxane [ 36 , 37 ], polyamide [ 38 ], polyethyleneimine [ 39 ], sodium alginate [ 40 , 41 ], polyvinyl alcohol [ 42 , 43 , 44 , 45 , 46 ], etc.…”
Section: Introductionmentioning
confidence: 99%